2021
DOI: 10.3390/ijerph182211757
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of Digital Game-Based Learning in Nursing and Occupational Therapy Degrees: A Comparative Study at the University of Burgos

Abstract: Teaching in higher education in the 21st century is moving towards e-Learning or b-Learning teaching models. This situation has increased due to the SARS CoV-2 health crisis. Therefore, teaching–learning models must be based on the use of active methodologies that facilitate students’ motivation to work in learning management systems (LMS). One of the most current resources is the digital game-based learning (DGBL) use, specifically in health sciences degrees (e.g., nursing). In this study, we worked with 225 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…Only one article combines face-to-face and computer-mediated interaction (Figure 3). There is still a predilection for face-to-face interaction, even though teaching in 21st-century higher education is moving towards e-Learning or b-Learning teaching models (Sáiz-Manzanares et al, 2021). This may happen because educational institutions have been slowly moving to transform their offerings towards e-learning and blearning.…”
Section: Discussionmentioning
confidence: 99%
“…Only one article combines face-to-face and computer-mediated interaction (Figure 3). There is still a predilection for face-to-face interaction, even though teaching in 21st-century higher education is moving towards e-Learning or b-Learning teaching models (Sáiz-Manzanares et al, 2021). This may happen because educational institutions have been slowly moving to transform their offerings towards e-learning and blearning.…”
Section: Discussionmentioning
confidence: 99%
“…The gendered dynamics of LMS adoption and use in STEM and non-STEM fields are also illuminated by Manzanares [9]. The research revealed that teacher and student use of learning objects in LMS varied by both experience and gender.…”
Section: Theoretical Frameworkmentioning
confidence: 93%
“…Two formats of training taking place at the same time can reduce the effectiveness of the training for both face-to-face and online audiences. A key challenge for trainers is ensuring synchronisation between online content and face-to-face sessions, as well as fostering interaction and collaboration among trainees in both contexts [46]. B-learning proves to be an effective approach for developing practical and theoretical competences.…”
Section: E-learning and B-learningmentioning
confidence: 99%